A cortical hierarchy of localized and distributed processes revealed via dissociation of task activations, connectivity changes, and intrinsic timescales - Ito, Takuya; Hearne, Luke J.; Cole, Michael W. (NeuroImage (Orlando, Fla.), 2020)
Many studies have identified the role of localized and distributed cognitive functionality by mapping either local task-related activity or distributed functional connectivity (FC). However, few studies have directly explored the relationship between a brain region’s localized task activity and its distributed task FC. Here we systematically evaluated the differential contributions of task-related activity and FC changes to identify a relationship between localized and distributed processes across the cortical hierarchy. We found that across multiple tasks, the magnitude of regional task-evoked activity was high in unimodal areas, but low in transmodal areas. In contrast, we found that task-state FC was significantly reduced in unimodal areas relative to transmodal areas. This revealed a strong negative relationship between localized task activity and distributed FC across cortical regions that was associated with the previously reported principal gradient of macroscale organization. Moreover, this dissociation corresponded to hierarchical cortical differences in the intrinsic timescale estimated from resting-state fMRI and region myelin content estimated from structural MRI. Together, our results contribute to a growing literature illustrating the differential contributions of a hierarchical cortical gradient representing localized and distributed cognitive processes. •Task activations and functional connectivity changes are negatively correlated across cortex.•Task activation and connectivity dissociations reflect differences in localized and distributed processes in cortex.•Differences in localized and distributed processes are associated with differences in intrinsic timescale organization.•Differences in localized and distributed processes are associated with differences in cortical myelin content.•Cortical heterogeneity in localized and distributed processes revealed by activity flow mapping prediction error.